# 3x(4y-6)=

## Simple and best practice solution for 3x(4y-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3x(4y-6)= equation:

Simplifying
3x(4y + -6) = 0
Reorder the terms:
3x(-6 + 4y) = 0
(-6 * 3x + 4y * 3x) = 0
(-18x + 12xy) = 0
Solving
-18x + 12xy = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), '6x'.
6x(-3 + 2y) = 0
Ignore the factor 6.
Subproblem 1Set the factor 'x' equal to zero and attempt to solve:
Simplifying
x = 0
Solving
x = 0
Move all terms containing x to the left, all other terms to the right.
Simplifying
x = 0
Subproblem 2Set the factor '(-3 + 2y)' equal to zero and attempt to solve:
Simplifying
-3 + 2y = 0
Solving
-3 + 2y = 0
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 3 + 2y = 0 + 3
Combine like terms: -3 + 3 = 0
0 + 2y = 0 + 3
2y = 0 + 3
Combine like terms: 0 + 3 = 3
2y = 3
Add '-2y' to each side of the equation.
2y + -2y = 3 + -2y
Combine like terms: 2y + -2y = 0
0 = 3 + -2y
Simplifying
0 = 3 + -2y
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.Solutionx = {0}`